Association between hepatitis C infection and number of screened blood unit transfusions in thalassemic children - Diah Asri Wulandari; Iesje Martiza; Yasmar Alfa; Dwi Prasetyo (Indonesian Pediatric Society Publishing House, 2016)
Background Donor blood screening test for antibody against hepatitis C virus (HCV) by third generation ELISA is widely used. However, there is still a window period during which a donor may already be infected despite a negative screening test. Objectives To determine the prevalence of hepatitis C infection in thalassemic children who had received screened donor blood and to seek the association between HCV infection and the number of blood unit transfusions received. Methods This was an analytic cross-sectional study. Sixty-seven children who had received third generation ELISA screened donor blood were examined for HCV antibody. The study was conducted in Hasan Sadikin General Hospital, Bandung, from January to March 2004. The prevalence of hepatitis C was presented in per- centage. The association between HCV infection and sex, age, interval between transfusions, and the number of blood unit trans- fusions received was determined by univariate analysis and logis- tic regression analysis. Results In univariate analysis, significant difference between HCV- infected and uninfected subjects was found in the mean age and mean number of blood units transfused (P<0.001). In logistic re- gression analysis, we found a significant association between the quantity of transfused blood with positive HCV antibody (P<0.001). The odds ratio for positive HCV antibody was 1.08 for each blood unit transfusion received (95%CI 1.02;1.14). The prevalence of hepatitis C in thalassemic children who received third generation ELISA screened blood was 22.4% (95%CI 12.4%;32.4%). This prevalence is lower than that in a previous study of thalassemic children receiving unscreened blood (50.8%). Conclusions The prevalence of HCV infection in thalassemic chil- dren who had received screened donor blood is 22.4%. HCV in- fection is significantly associated with the number of screened blood unit transfusions